Upaya Peningkatan Productivity Mesin Extrusion 2500 Menggunakan Metode Overall Equipment Effectiveness (OEE) dan Six Big Losses Studi Kasus PT XYZ - Arif Nuryono, S.T., M.T.; Alloysius Vendhi Prasmoro, S.T., M.T; Gusti Andhika Aji (JURNAL BHARA PETRO ENERGI, 2022)
PT. XYZ is engaged in manufacturing in making aluminum profile products during the last one year period. XYZ company did not reach its production target by an average of 6.24%. As for the reasons why the production target did not reach the target, one of them was due to the high downtime of the extrusion machine 2500 which exceeded the company standard, namely 7800 minutes per year, the downtime of the extrusion machine 2500 in the last year was 9807 minutes. The purpose of this study is to reduce the downtime value of the extrusion machine using the OEE method (overall equipment effectiveness), to increase the productivity of the extrusion machine 2500 from the results of the analysis of six big losses and identify the main causes of downtime of the extrusion 2500 machine. The results show that the OEE value of the extrusion machine. 2500 by 45. 61% where this value is still below the ideal OEE average standard, namely 85%. The main cause of downtime is due to seven factors that dominate the causes of downtime, namely log heater 2230 minutes with 11 events, puller 1740 minutes with 11 events, dummi block 1390 with 4 events, loader 710 minutes with 4 events, finish cut 540 minutes with 3 events, stem 450 minutes with 2 events, 360 minutes table with 1 event. Based on the results of the calculation of six big losses, the results of downtime values: equipment failure losses 3,81%, setup and adjustment losses 3,95%, speed losses: idle and minor stoppage 3,03%, reduced speed losses 46,51, quality losses: defect losses 0,13%, reduced yield 0 %. The recommendation for improvement is to conduct special training, give warnings to operators who are not disciplined. Reference: Ahuja, I. P. S., Khamba, J. S. (2008). Total Productive Maintenance Literature Review and Directions. International Journal of Quality and Reliability Management, 25 (7), 709-756. Atmaja, L. T., Supriyadi, E., & Utaminingsih, S. (2018). Analisis Efektivitas Mesin Pressing Ph-1400 Dengan Metode Overall Equipment Effectiveness ( Oee ) Di Pt . Surya Siam Keramik. 1. Anggraini, M., Widya, M. W., Edy, K. F. B. (2017). Implementasi Metode Overall Equipment Effectiveness Dalam Menentukan Produktivitas Mesin Rotary Car Dumper. Seminar dan Konferensi Nasional IDEC 2017, 1 (1), 78-87. Hadi, S. (2019). Perawatan Dan Perbaikan Mesin Industri. Yogyakarta: Andi. Hamdy, I. M., Azizi, A. (2017). Analisis Nilai Overall Equipment Effectiveness (OEE) Pada Mesin Ripple Mill. Jurnal Hasil Penelitian dan Karya Ilmiah Dalam Bidang Industri, 3 (1), 53-58. Hamid, A., & Purnomo, S. A. (2018). Analisa Efektivitas Kinerja Mesin Turning Star SB-16 Dengan Metode Total Productive Maintenance ( TPM ) di PT Mitsuba Indonesia Dosen Teknik Industri Universitas Pamulang. Jitmi, 1 (1), 50 - 63. Hazmi, M. F., Juniani, A. I., Budiyantoro, E. N. (2017). Analisis Perhitungan OEE Dan Six Big Losses Terhadap Produktivitas Mesin Bottomer Line 4 PT. IKSG Tuban. Jurnal Conference on Safety Engineering and Application, 1 (1), 161-166. Heru, W., Ferdiansyah, F. (2018). Analisis Efektifitas Mesin Roughing Mill dengan Metode Overall Equipment Effectiveness (OEE). Jurnal Industri Manufacturing, 3 (2), 67-78. Jannah, R. M., Supriyadi., Nalhadi, A. (2017). Analisis Efektivitas Pada Mesin Centrifugal Dengan Menggunakan Metode Overall Equipment Effectiveness (OEE). Seminar Nasional Riset Terapan, 1 (1), 170-175. Karismawan, F. (2015). Pengukuran Kinerja Mesin Perusahaan Menggunakan Overall Equipment Effectiveness dan Usulan Perbaikan Menggunakan Diagram Sebab Akibat (Fish Bone) Pada CV. Jati Makmur Pasuruan. Jurnal Manajemen Teori dan Terapan, 1 (2), 107-115. Kholil, M., Maulidina, A. D., Rimawan, E. (2016).Analisa Total Productive Maintenance Terhadap Produktivitas Kapal Armada Menggunakan Metode Overall Equipment Effectiveness pada PT. Global Trans Energy International. Jurnal of Industrial Engineering and Management Systems, 9 (1), 1-18. Kholisdiantoro, S. (2016). Usulan Perbaikan Untuk Peningkatan Efektivitas Kinerja Mesin Crusher di Incinerator 2 Dengan Metode Overall Equipment Effectiveness. Teknik Industri. Universitas Bhayangkara Jakarta Raya. Rahmadhani, D. F., Taroepratjeka, H., & Fitria, L. (2014). Usulan Peningkatan Efektivitas Mesin Cetak Manual Menggunakan Metode Overall Equipment Effectiveness (OEE) (Studi Kasus Di Perusahaan Kerupuk TTN). Jurnal Online Institut Teknologi Nasional, 2 (4), 156 –165. Soemohadiwidjojo, A. T. (2017). Six Sigma metode pengukuran kinerja perusahaan berbasis statistik. Jakarta: Raih asa sukses (RAS). Suwardiyanto, P., Siregar, D., Umar, D. (2020). Analisis Perhitungan OEE dan Menentukan Six Big Losses pada Mesin Spot Welding Tipe X. Journal of Industrial and Engineering Sistem, 1 (1), 11-20.